Civic Value and Political Interest as Determinants of Political Participation Among Primary School Teachers in Oyo State - Muraina Kamilu Olanrewaju; Muraina Kehinde Maruf; Oladele Omolare (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2023)
The purpose of this study was to examine civic value and political interest as determinants of political participation among primary school teachers in Oyo state. Five hundred participants constituted the study’s sample out of which only 476 were used after data administration. Both the independent and dependent variables were measured with validated instruments with 0.91 reliability co-efficient and the data obtained was analyzed using Pearson Product Moment Correlation (PPMC) Statistical method. Two research hypotheses were formulated and tested at 0.05 level of significance. The result showed that there was significant relationship between civic value and political participation among primary school teachers (r= .813; p<0.05) as well as between political interest and political participation among primary school teachers (r= .701; p<0.05). The implication of this showed that civic value and political interest had significant impacts on political participation among primary school teachers. In view of these findings, it was recommended that educational stakeholders should intensify their effort to institute a culture of civic value in the institution so as to improve on the level of political participation among primary school teachers.